Development of CaCO3 novel morphology through crystal lattice modification assisted by sulfate incorporation and vibration - Mangestiyono, Wiji; Jamari, J.; Bayuseno, A.P.; Muryanto, S. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
CaCO3 has long been used as a filler to increase many properties of the material. The filler commonly consists of inexpensive materials that replace some volume of the more expensive materials, which can reduce the cost of the final product. CaCO3 morphology that can be used as filler depends on the filler's function, such as filler for paper, paint, rubber, or composite. A filler for composite materials is needed to increase interfacing interactions between the particulate fillers and the matrix. So, the particulate in a broader shape will be the best choice to function for such filler. In this research, in an attempt to increase the interfacing interaction, CaCO3 morphology was modified in such a way through crystal lattice modification assisted by sulfate incorporation and vibration. SEM analysis was implemented, and showed that the research successfully produced novel morphology in branchy-like polymorphs. FTIR analysis also proved that the crystal lattice has been modified. The morphology in branchy-like polymorph is supposed to increase interfacing interaction between CaCO3 as the filler and the matrix. The methods are also supposed to be implemented as the research is scaled up to commercial scale.